Identifying Key Psychological Predictors of Mind–Body Health Discrepancy - Lee , Angel; Wong , Yoko; Neo, Xian Seng (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study aimed to identify the key psychological predictors that contribute to discrepancies between perceived mental well-being and physical health among adults in Singapore. A qualitative research design with an interpretive phenomenological approach was adopted to explore the psychological mechanisms underlying mind–body health incongruence. A total of 21 adult participants (12 females, 9 males; aged 26–54 years) were recruited through purposeful sampling based on self-reported differences between their psychological and physical health experiences. Data were collected through semi-structured, in-depth interviews lasting 60–90 minutes and analyzed using Braun and Clarke’s thematic analysis framework with the aid of NVivo 14 software. Theoretical saturation was achieved after the 21st interview. Rigor was ensured through member checking, audit trails, and peer debriefing. The analysis revealed four major psychological domains explaining the mind–body health discrepancy: (1) Emotional dysregulation and somatic sensitivity, reflecting the translation of unprocessed emotions into bodily symptoms; (2) Cognitive appraisal and belief systems, indicating that maladaptive health beliefs, perfectionism, and mind–body dualism contribute to misaligned health perceptions; (3) Behavioral and lifestyle misalignment, showing inconsistent self-care and maladaptive coping strategies that sustain perceptual dissonance; and (4) Interpersonal and sociocultural determinants, encompassing social expectations, family communication patterns, and cultural norms that reinforce emotional suppression and health misperception. Collectively, these themes suggest that subjective health perception is shaped more by cognitive–emotional regulation and social context than by biological status. The study underscores that mind–body health discrepancy arises from the convergence of emotional, cognitive, behavioral, and sociocultural factors. Enhancing emotional regulation, cognitive flexibility, and social support systems may reduce such incongruence and promote holistic well-being. These findings provide a conceptual foundation for integrative psychological and medical interventions.